Seeking Justice in Ugandan Courts: Amnesty and the Case of Thomas Kwoyelo - Kirsty McNamara (Washington University Global Studies Law Review, 2013)
Part I of this Note outlines the background of the conflict in Uganda, the problems and benefits that came with the ICC intervention in 2003, the establishment of the ICD, and an overview of the Amnesty Act of 2000. Part II focuses specifically on the facts and holdings of the Kwoyelo case, and will evaluate, in light of this precedent, whether the ICD can truly allow Uganda to fulfill its obligations under international and domestic law. Finally, this Note concludes with a discussion about Uganda’s international obligations and the effectiveness of the Amnesty Act and recommends various ways for the Ugandan government to amend the law in order to preserve amnesty while effectively pursuing justice.
Keywords: amnesty; criminal justice; Uganda; courts; Thomas Kwoyelo; ICC; international criminal court; international law; domestic law